Design And Development Of Start-Up Company Financial Health Prediction Application Using Z-Score Modification Method With SDLC Approach - Maulana, Danis (Jurnal Entrepreneur dan Entrepreneurship, 2022)
50% of start-ups globally fail in the first 4 years. The 2 main causes are working capital and the inability of resources to manage it. Financial distress is the initial stage of bankruptcy, which is marked by the uncertainty of profitability and the company's inability to pay its obligations. Therefore, it is very important for start-ups, especially CV Bee Digital Prestasi Nusantara, to pay attention to the level of financial health in order to maintain the company's existence. This study aims to overcome these problems, by designing a prototype application to predict the financial health of the start-up company to provide an early warning, support company acceleration, and anticipate bankruptcy. This application prototype is designed using the SDLC Waterfall method approach with the PHP Native programming language, while the calculation of financial health uses the Modified Z-Score method. With this financial prediction application, it is hoped that start-up companies will easier to know the condition of their financial health, be able to provide policy recommendations and actions that must be taken. So that start-up companies, especially CV Bee Digital Prestasi Nusantara, can have better financial conditions to maintain their company's existence.